PRIMING BENIH KEDELAI (Glycine max L.) YANG TELAH MENGALAMI PENYIMPANAN DENGAN MENGGUNAKAN EKSTRAK DAUN KELOR - Alimuddin, Suraedah; Ralle, Andi; Asmilawati, Asmilawati (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2025)
Soybean seeds are highly prone to deterioration, as indicated by a decline in viability and vigor during natural storage. One approach to improve the physiological performance of deteriorated seeds is seed priming using Moringa oleifera leaf extract. This study aimed to evaluate the effects of concentration and soaking duration of M. oleifera leaf extract on the viability and vigor of soybean seeds after six months of natural storage.  The experiment was conducted at the Laboratory of Biotechnology and Crop Production, Faculty of Agriculture, Universitas Muslim Indonesia, using a completely randomized design (CRD) with a two-factor factorial arrangement. The first factor was the concentration of M. oleifera leaf extract (0%, 5%, 10%, and 15%), while the second factor was soaking duration (2 hours, 4 hours, and 6 hours). Each treatment combination was replicated three times.  The results showed that priming with moringa leaf extract at 5% and 10% significantly improved germination percentage, root length, and seedling dry weight compared with the control. Seed priming with a soaking duration of 4 hours produced the highest root length and seedling dry weight, whereas soaking for 6 hours reduced seed performance. The interaction between extract concentration and soaking duration had no significant effect on any of the observed parameters.